Organizational Innovativeness and its Results: A Qualitative Analysis of SME Hotels in Vienna. (May 2016) - Binder, Petra; Mair, Michael; Stummer, Katharina; Kessler, Alexander
In the face of increasingly intense competition and saturated markets, competitive advantages through innovation (also) in tourism are continuously gaining importance for business survival and growth. Using a qualitative approach to investigate 12 small and medium enterprises in the Viennese hotel sector, this study focuses on identifying the extent to which different forms of organizational innovativeness lead to different innovation results. On the basis of the analysis, four types of innovation results (systematic renewal, systematic improvement, adaptation, and startups) can be identified. These innovation results can be traced back to different configurations of organizational innovativeness. The study shows that systematic renewal is promoted by a combination of all dimensions of organizational innovativeness (willingness to innovate, ability to innovate, and possibility of innovation).